Comparison of the Charpy Resilience of Two 3D Printed Materials: A Study on the Impact Resistance of Plastic Parts - Zisopol, Dragos Gabriel; Ion, Nae; Portoaca, Alexandra Ileana (Engineering, Technology & Applied Science Research, 2023)
Charpy impact testing is a widely used method for the evaluation of the toughness of materials, including 3D-printed plastic parts. This study performed Charpy test on 3D-printed samples made of PLA and ABS. Factors such as layer thickness and infill percentage varied (0.10, 0.15, and 0.20mm layer height and 50, 75, and 100% infill percentage) to investigate how they affect the mechanical properties of 3D printed parts, including their toughness.